Knowledge, attitudes, and practices of operating room technologists in preventing pressure ulcers in surgical patients - Tayyebeh Azarmehr; Najmeh Ghiami Keshtgar (Journal of Preventive and Complementary Medicine)
Background: Pressure ulcers are common among surgical patients and can lead to increased complications, prolonged hospital stays, and higher treatment costs. Operating room technologists play a crucial role in preventing the development of these conditions.Objective: This study aimed to evaluate the knowledge, attitudes, and practices of operating room technologists in educational hospitals in Zahedan, Iran, regarding pressure ulcer prevention.Methods: This descriptive-analytical study was conducted cross-sectionally from September to December 2022. A census sampling method was employed, including 58 operating room technologists from the operating rooms of educational hospitals affiliated with Zahedan University of Medical Sciences, Iran. Data were collected using a researcher-designed questionnaire that assessed knowledge, attitudes, and practices related to pressure ulcer prevention. The questionnaire was validated. The collected data were analyzed using descriptive statistics, independent t-tests, and ANOVA in SPSS version 21.Results: The mean scores and standard deviations for knowledge, attitudes, and practices were 38.8±7.15, 33.6±7.9, and 23.4±5.4, respectively. Most operating room technologists exhibited a positive attitude, relatively adequate knowledge, and moderate practices concerning pressure ulcer prevention. The results revealed a significant relationship between the knowledge score and the age of the technologists (p<0.05).Conclusion: This study highlights the vital role of operating room technologists in preventing pressure ulcers in surgical patients. To enhance the quality of care, it is recommended that topics related to pressure ulcer prevention and management be integrated into both the educational curriculum and in-service training programs.